Analysing Web 2.0 Usage of High School Students in the Partium Region before the Covid-19 Pandemic (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2020)
The rapid pace of technological development has had a significant impact on education. Thanks to it and the widespread use of information and communication technology tools, Web 2.0 has emerged and entered an unpredictable path, as the environment in which students of the present age (members of the Z-generation) learn and are taught and trained. As a result, formal teaching is gradually replaced by open and virtual learning environments, which have made interactive learning environments and user-generated content a prominent issue. It seems obvious that these phenomena and their use in learning are closely intertwined with continuous feedback mechanisms. Their examination is important because by understanding the effects of these processes, since we can gain a more comprehensive picture of their role in education, especially in the case of learning activities using ICT. In the current research, the focus is on the use of Web 2.0 tools by students. Although the research was originally designed as a stand-alone project, we had to re-evaluate our perspectives because of the pandemic that occurred in the meantime. At present, we can rather consider it as a preliminary study, which will be followed by a new query in the autumn.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.